2015
DOI: 10.5301/tj.5000426
|View full text |Cite
|
Sign up to set email alerts
|

Misregulation of the Dependence Receptor DCC and its Upstream lincRNA, LOC100287225, in Colorectal Cancer

Abstract: Our study demonstrated the concurrent misregulation of DCC and LOC100287225 in colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…GO and KEGG databases were used to conduct GO functional analysis and KEGG signaling pathway analysis on the seven genetic markers so as to establish a primary apoptotic regulatory network, which showed that DCC was involved in the apoptotic signaling pathway with positive regulation. And over these years DCC was reported as one of the key tumor suppressor genes (Kazemzadeh et al, 2015) and was closely correlated to growth and development of colorectal cancer. And it was found that DCC gene can inhibit cell proliferation and cause degraded carcinoembryonic antigen (CEA) expression in rectal cancer cell line SW1116 (Jiang et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…GO and KEGG databases were used to conduct GO functional analysis and KEGG signaling pathway analysis on the seven genetic markers so as to establish a primary apoptotic regulatory network, which showed that DCC was involved in the apoptotic signaling pathway with positive regulation. And over these years DCC was reported as one of the key tumor suppressor genes (Kazemzadeh et al, 2015) and was closely correlated to growth and development of colorectal cancer. And it was found that DCC gene can inhibit cell proliferation and cause degraded carcinoembryonic antigen (CEA) expression in rectal cancer cell line SW1116 (Jiang et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, lincRNAs are associated with various cancers, including prostate cancer 16 , breast cancer 18 , colorectal cancer 20 , 21 , ovarian cancer 22 , and bladder cancer 24 , and also associated with disease progression, for example, the HOTAIR (HOX transcript antisense RNA) is highly expressed in the breast cancer and is a predictor for metastasis formation 39 , indicating that lincRNAs could be applied to the prediction and treatment of cancers. However, chicken lincRNAs were only reported to participate in MDV tumorigenesis 36 .…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that DCC positively regulated the apoptotic signal pathway. It has been found in recent years that DCC is the largest human tumor suppressor gene (Kazemzadeh et al, 2015) closely related to onset and development of colorectal cancer. PTEN is an important tumor suppressor gene with phosphatase activity.…”
Section: Discussionmentioning
confidence: 99%